Expression and localization of Inter-alpha Inhibitors in rodent brain. (2nd June 2016) - Chen, X.; Rivard, L.; Naqvi, S.; Nakada, S.; Padbury, J.F.; Sanchez-Esteban, J.; Stopa, E.G.; Lim, Y.-P.; Stonestreet, B.S.
Highlights: Proteins and mRNA of IAIP light and heavy chains are expressed in mouse neurons. Proteins of IAIPs were detected in cultured rat neurons, microglia, and astrocytes. IAIP immunoreactivity was detected in different brain regions. IAIPs are expressed in a wide variety of brain cells and regions in rodent CNS. Abstract: Inter-alpha Inhibitor Proteins (IAIPs) are a family of related serine protease inhibitors. IAIPs are important components of the systemic innate immune system. We have identified endogenous IAIPs in the central nervous system (CNS) of sheep during development and shown that treatment with IAIPs reduces neuronal cell death and improves behavioral outcomes in neonatal rats after hypoxic–ischemic brain injury. The presence of IAIPs in CNS along with their exogenous neuroprotective properties suggests that endogenous IAIPs could be part of the innate immune system in CNS. The purpose of this study was to characterize expression and localization of IAIPs in CNS. We examined cellular expressions of IAIPs in vitro in cultured cortical mouse neurons, in cultured rat neurons, microglia, and astrocytes, and in vivo on brain sections by immunohistochemistry from embryonic (E) day 18 mice and postnatal (P) day 10 rats. Cultured cortical mouse neurons expressed the light chain gene Ambp and heavy chain genes Itih-1, 2, 3, 4, and 5 mRNA transcripts and IAIP proteins. IAIP proteins were detected by immunohistochemistry in cultured cells as well as brain sections from E18 mice and P10 rats. Immunoreactivity was found in neurons, microglia, astrocytes and oligodendroglia in multiple brain regions including cortex and hippocampus, as well as within both the ependyma and choroid plexus. Our findings suggest that IAIPs are endogenous proteins expressed in a wide variety of cell types and regions both in vitro and in vivo in rodent CNS. We speculate that endogenous IAIPs may represent endogenous neuroprotective immunomodulatory proteins within the CNS.